Data sharing in biological anthropology. (28th February 2022) - Mulligan, Connie J.; Boyer, Doug M.; Turner, Trudy R.; Delson, Eric; Leonard, William R.
Abstract: Open data sharing democratizes science by making data more equitably available throughout the world. Furthermore, open data sharing improves the reproducibility and quality of research and enables new collaborations powered by the freely available data. Open data are defined as data that can be freely used, reused, and redistributed by anyone. For an interdisciplinary field like biological anthropology, data sharing is critical since one person cannot easily collect data across the domains relevant to our field. The goal of this paper is to encourage broader data sharing in our discipline by exploring the state of data sharing in the field of biological anthropology. Our paper is divided into four parts: the first section describes the benefits, challenges, and emerging solutions to open data sharing; the second section presents the results of our data archiving and sharing survey that was completed by over 700 researchers; the third section presents personal experiences of data sharing by the authors; and the fourth section discusses the strengths of different types of data repositories and provides a list of recommended data repositories.